Distinguishing Between Monetary and Nonmonetary Assets and Liabilities in General Price-Level Accounting. - Heath, Loyd C. (The Accounting Review, 1972)
Abstract The purpose of this paper is to clarify and sharpen the distinction between monetary and non-monetary assets and liabilities for general price-level accounting. This is done in several steps. First, the conceptual basis of general price-level accounting is examined and the distinction between general price-level accounting and conventional accounting is discussed. Second, an example is introduced to illustrate the nature of general price-level gains and losses and how these gains and losses differ from gains and losses now reported in general price level-accounting. Third, the definition used by several authorities for distinguishing between monetary and non-monetary items are examined and evaluated critically in the light of the theoretical concepts developed earlier. The paper concludes with proposed new criteria for distinguishing between monetary and non monetary items in general price-level accounting. If financial statements are to be of maximum benefit in providing a starting point for predicting future profits and losses, gains and losses due to one causal force should be reported separately from those due to other forces.